2020
DOI: 10.4218/etrij.2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

A supervised‐learning‐based spatial performance prediction framework for heterogeneous communication networks

Abstract: In this paper, we propose a supervised‐learning‐based spatial performance prediction (SLPP) framework for next‐generation heterogeneous communication networks (HCNs). Adaptive asset placement, dynamic resource allocation, and load balancing are critical network functions in an HCN to ensure seamless network management and enhance service quality. Although many existing systems use measurement data to react to network performance changes, it is highly beneficial to perform accurate performance prediction for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…If a security problem occurs in a certain link, it may have a greater impact on the operation of the system. Such as chip quality, Trojan hardware, etc [5]. Relevant studies have shown that the use of machine learning technology can help chips solve security problems, and can quickly identify inferior chips and hardware Trojans by performing variable signal analysis, image recognition, etc.…”
Section: Chip Securitymentioning
confidence: 99%
“…If a security problem occurs in a certain link, it may have a greater impact on the operation of the system. Such as chip quality, Trojan hardware, etc [5]. Relevant studies have shown that the use of machine learning technology can help chips solve security problems, and can quickly identify inferior chips and hardware Trojans by performing variable signal analysis, image recognition, etc.…”
Section: Chip Securitymentioning
confidence: 99%
“…A RTIFICIAL intelligence (AI) and machine learning (ML) are promising technologies for future wireless networks [1]- [4]. Recently, the IEEE 802.11 working group approved the formation of a topic interest group (TIG) for the AI/ML use in the IEEE 802.11 [5].…”
Section: Introductionmentioning
confidence: 99%